2019
DOI: 10.3389/fpsyg.2019.01317
|View full text |Cite
|
Sign up to set email alerts
|

When Error Learning Orientation Leads to Learning From Project Failure: The Moderating Role of Fear of Face Loss

Abstract: As the importance of failure is widely recognized, there is increasing research interest in the antecedents of learning from failure. Basing on affective event theory, the current study cast light on individuals’ cognition of error and proposed that employees with higher levels of error learning orientation tend to show more positive grieving after project failure, which in turn increases their learning from failure. Using a sample of 752 employees from 140 project teams, we found empirical evidence to support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 43 publications
4
25
0
1
Order By: Relevance
“…This is very different from the research conclusions of previous scholars. Most of the previous scholars have confirmed that positive grieving has a positive effect (e.g., learning from failure) ( Wang et al, 2019 ). Our research confirms that positive grieving may also have a negative effect, which provides a theoretical and practical basis for follow-up scholars to further explore.…”
Section: Analysis and Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…This is very different from the research conclusions of previous scholars. Most of the previous scholars have confirmed that positive grieving has a positive effect (e.g., learning from failure) ( Wang et al, 2019 ). Our research confirms that positive grieving may also have a negative effect, which provides a theoretical and practical basis for follow-up scholars to further explore.…”
Section: Analysis and Discussionmentioning
confidence: 96%
“…), the organization’s management style (e.g., error management culture), and individual characteristics (e.g., resilience), there is little research on the role of failure-induced transitional emotions (i.e., positive grieving) in individual learning process ( Zhao, 2011 ; Fang He et al, 2018 ). As a normal emotion after negative events occur, previous research shows that positive grieving may have an impact on learning behaviors ( Wang et al, 2019 ). However, few scholars use it as a moderating variable to study its influence on the mechanism of individual behavior and its antecedent variables.…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, cultural differences also need to be considered when exploring the role of shame. In fact, some scholars have combined face to learning from failure-related research (e.g., Wang et al, 2019). However, there is still a lack of further description of its specific mechanism.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%